Kreativitas Guru dalam Membimbing Kelompok Kecil pada Pendidikan Anak Usia Dini - Suraya Suraya; Riani Agustina; Normaliza Normaliza; Nur Jamiah; Kholidar Nur (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This research aims to analyze the role of teacher creativity in guiding small groups in Early Childhood Education (PAUD). Teacher creativity is very important in facilitating the social, emotional and cognitive development of early childhood. This research uses a qualitative approach with a case study method involving observations and interviews with several PAUD teachers. The research results show that teacher creativity in designing learning activities that are fun, interesting and appropriate to children's development can increase children's overall involvement and development. Therefore, there needs to be more effort to improve the quality of teacher creativity in the small group learning process in PAUD.